Experimental work of effect of openings on the post-tensioned flat slab - Amal Zamrawi; Ata El-Kareim Shoeib; Angelos Ibrahim; Samir M. Ahmed (Fracture and Structural Integrity)
This study aims to evaluate the effect of various parameters on the behavior of the reinforced concrete flat slabs and the contribution of each design element in the punching shear strength. This research presents experimental results of tested post-tensioned flat slabs with opening under concentric compressive load. The developed post-tensioned flat slabs are to ensure adequate punching shear strength capacity. The experimental work consisted of eight specimens of post-tensioned reinforced concrete flat slabs which classified into groups. All slabs had the same dimension and reinforcement. The slabs had dimensions with a 1750 mm length and 1750 mm width, to study the behavior of post-tensioned flat slab with/out openings under the concentrated load and punching influence.